Family assessment handbook an introduction and practical guide to family assessment - Thomlison, Barbara (Boston, MA Cengage Learning, 2016)
Providing practical information and theoretical foundations established on evidence-based methodology, FAMILY ASSESSMENT HANDBOOK: AN INTRODUCTION AND PRACTICAL GUIDE TO FAMILY ASSESSMENT, Fourth Edition presents a step-by-step approach to family practice that teaches students to be critical thinkers for the study and practice of family work. Students learn to develop multiple views of a problem and to integrate common skills from traditional, post-modern, and evidence-based systemic family models. The evidence base for this edition reflects a resilience-based and integrated family systems approach to practice. The first part of the book presents relevant systems theory and concepts that guide family practice, providing a foundation to assist students in case assessment conceptualization. The second part has been revised with updated evidence-based assessment measures and interventions for common family issues. The third part is updated to address the role of reflection and disclosure writing skills for engaging families. New cases and revised exercises are in Part Four. Examples of assessment reports and intervention contracts, as well as capstone assessment case presentations, are now in Appendices.
Appendices: pages 245-265.
Includes bibliographical references (pages 267-279) and index.
Keywords: Family social work; Family assessment